Vlakno cave on Dugi otok (In situ, 2024)
The paper presents the results of archaeological research conducted in the Vlakno cave on Dugi otok during 2022.Vlakno cave is located in the central part of Dugi otok opposite the island of Rava. With 40 m2 of usable space, combined with a large entrance facing southeast and a water source nearby, the cave proved to be an excellent dwelling place for smaller communities during the late Palaeolithic and early Mesolithic. The stratigraphic sequence of Vlakno cave is dominated by layers with finds of the Epigravettian culture, from the deepest levels reached. This year's campaign was focused on investigating those dating back to 17,000 years ago.
Keywords: cave Vlakno; Dugi otok; Palaeolithic; Epigravettian